New upper limits for hydrogen halides on Saturn derived from Cassini-CIRS data - Teanby, N; Fletcher, L; Irwin, P; Fouchet, T; Orton, G (2006)
Far infrared spectra (10-600 cm-1) from Cassini's Composite InfraRed Spectrometer (CIRS) were used to determine improved upper limits of hydrogen halides HF, HCl, HBr, and HI in Saturn's atmosphere. Three observations, comprising a total of 3088 spectra, gave 3σ upper limits on HF, HCl, HBr, and HI volume mole fractions of 8.0 × 10-12, 6.7 × 10-11, 1.3 × 10-10, and 1.4 × 10-9, respectively, at the 500 mbar pressure level. These upper limits confirm sub-solar abundances of halide species for HF, HCl, and HBr in Saturn's upper atmosphere-consistent with predictions from thermochemical models and influx of material from meteoroids. Our upper limit for HCl is 16 times lower than the tentative detection at 1.1 × 10-9 reported by Weisstein and Serabyn [Weisstein, E.W., Serabyn, E., 1996. Icarus 123, 23-36]. These observations are not sensitive to the deep halide abundance, which is expected to be enriched relative to the solar composition. © 2006 Elsevier Inc. All rights reserved.